2016
DOI: 10.18632/oncotarget.11435
|View full text |Cite
|
Sign up to set email alerts
|

CD73 is associated with poor prognosis in HNSCC

Abstract: CD73 is a cell surface immunosuppressive enzyme involved in tumor progression and metastasis. While patients whose cancer cells express elevated CD73 are typically associated with an unfavorable outcome, the clinical impact of CD73 expression in patients with Head and neck squamous cell carcinoma (HNSCC) remains unclear. In the present study, we investigated the prognostic significance of CD73 in HNSCC using gene and protein expression analyses. Our results demonstrate that high levels of CD73 are significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 43 publications
5
50
1
Order By: Relevance
“…Conversely, it has also been reported that inosine-mediated activation of the A3R can enhance melanoma cell proliferation through activation of the ERK pathway [100] and a cytoprotective role for the A3R has also been described [101]. Similarly, activation of the A3R has been suggested to enhance the migration or invasion of tumor cells [73,102,103]. Notably, in one study, divergent effects of A3R activation (via IB-MECA stimulation) on proliferation were observed in two colorectal cancer lines.…”
Section: Expression Of Adenosine Receptors and Signaling Pathways In mentioning
confidence: 95%
“…Conversely, it has also been reported that inosine-mediated activation of the A3R can enhance melanoma cell proliferation through activation of the ERK pathway [100] and a cytoprotective role for the A3R has also been described [101]. Similarly, activation of the A3R has been suggested to enhance the migration or invasion of tumor cells [73,102,103]. Notably, in one study, divergent effects of A3R activation (via IB-MECA stimulation) on proliferation were observed in two colorectal cancer lines.…”
Section: Expression Of Adenosine Receptors and Signaling Pathways In mentioning
confidence: 95%
“…CD73-deficient mice were demonstrated to sustain activated antitumor immunity, influencing neovascularization, tumor growth and metastasis [119,120]. CD73 inactivation was proved to inhibit progression of breast cancer and head and neck squamous cell carcinoma [121,122]. Likewise, anti-CD73 blocking antibody was also documented to impact spontaneous lung metastasis and decrease circulation capability of cancer cells [4].…”
Section: Cd39 and Cd73 As Tumor Therapeutic Targetsmentioning
confidence: 99%
“…1 Ecto-5 0 -nucleotidase (CD73), a 70 kDa glycosylated protein bounding to the outer surface of the plasma membrane by a glycosyl phosphatidyl inositol (GPI) anchor, is over-expressed in a variety of tumors, including breast cancer. [2][3][4][5] Major function of CD73 is catalyzing extracellular 5 0 -AMP to adenosine that plays important roles in many physiological and pathophysiological circumstances through adenosine receptor (A1, A2A, A2B and A3 AR). 6 Up-regulation of CD73 is associated with highly invasive cancer phenotype, drug resistance and tumor-promoting functions.…”
mentioning
confidence: 99%